Hubungan Antara Tingkat Pengetahuan Dan Sikap Masyarakat Tentang Penyakit Filariasis Dengan Tindakan Masyarakat Dalam Pencegahan Filariasis - Idia - Lusi; Gamya Tri Utami; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to identify the relationship between level of knowledge and people’s attitude about filariasis with the people actions of filariasis prevention. The method of this research was descriptive correlative with cross sectional approach. The sampling technique was stratified random sampling with 100 people in Pulau Padang Singingi sub-district Kuantan Singingi regency. The measurement instrument of this research was questionnaire and observation sheet that have tested with validity and reliability (r > 0,444). The univariate analysis was done by looking at the distributions of frequencies dan bivariate analysis was done by using chi-square test. The results showed that there is a correlation between level of knowledge of the peoples about filariasis and the people actionsoffilariasis prevention (pvalue = 0,035) and there is no correlation between attitude of the people about filariasis disease and the people actionsoffilariasis prevention (p value= 0,972). Based on theseresults, it recommended tothehealth care provider (puskesmas) to increase health promotions about the filariasis disease prevention with variety of media such as pictures or videos so that people are motivated to do the prevention of filariasis. Keywords: Action, attitude, filariasis, level of knowledge.